Problems of Child Rearing - A Comparative Study on Working and Non Working Women - R. , Jani Jasmine; H. , Deepa (International Journal of Psychosocial Rehabilitation, 2020)
This comparative study was undertaken to study the problems of child rearing for working and non-working women. The sample of the study consists of 150 working women and 150 non-working women from Kanyakumari district While selecting the sample, the weight was given to factors such as age, location, religion, community and type of family. The normative survey method was used in this study. To collect data, the interview technique was used to illiterate women and then questionnaire was given to literate women. The major statistical techniques used for the study are percentage, Arithmetic mean, standard deviation, t-test and ANOVA. The results shows that there existed significant difference between working and non-working women in their problems related with child rearing practices, health of children, educational assistance of their children, and leisure time activities of their children. These results highlight that working and nonworking women of Kanyakumari district have problems in child rearing. Working women poses problems related to educational assistance and leisure time activities. Working women do not possess problem related with the health of their children. Non-working women poses problem related to the health of their children and educational assistance. They do not possess problem related with leisure time activities.